Internalization of Akhlakul karimah Values in Children Through Religious Drama Cinema: An Analytical Study of The Film “Merindu Cahaya De Amstel” - Wanda Nabila Ma’wadah; Happy Susanto; Aldo Redho Syam; Muhammad Arinal Haq (ADPISI (Asosiasi Dosen Pendidikan Agama Islam Se-Indonesia), 2026)
The digital era has exacerbated challenges in moral education for the younger generation, creating a need for innovative and effective learning media. This study examines the process of internalizing noble moral values ​​akhlakul karimah in children through the medium of religious drama cinema, focusing specifically on the film “Merindu Cahaya de Amstel”. The research aims to identify the Islamic moral values ​​manifested in the film's narrative and to analyze their relevance to the development of contemporary Islamic education in Indonesia. A qualitative research approach was employed, utilizing hermeneutics and content analysis. Data collection involved the systematic observation of scenes and character dialogue, reinforced by triangulation through a comprehensive review of Islamic ethics literature. The findings identify five fundamental moral values—honesty, patience, responsibility, compassion, and humility—represented through the spiritual journey of the protagonist, Khadijah, as she navigates various social challenges. The study affirms that religious drama cinema serves as a potent pedagogical medium for facilitating the internalization of character values ​​by presenting them within contextual and inspiring narratives. The research highlights the urgent need to integrate film media into formal and informal educational frameworks to cultivate a generation that is not only morally steadfast but also capable of adapting to the complexities of the modern era.